2023
DOI: 10.3390/antiox12061245
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Rich Water Ameliorates Metabolic Disorder via Modifying Gut Microbiota in Impaired Fasting Glucose Patients: A Randomized Controlled Study

Abstract: Objective: Molecular hydrogen (H2) exhibits antioxidant, anti-inflammatory and anti-apoptotic effects, and has shown benefits in glucose and lipid metabolism in certain animal metabolic disorder models. However, the potential benefits of H2 treatment in individuals with impaired fasting glucose (IFG) has seldom been studied. This randomized controlled study (RCT) aims to investigate the effects of hydrogen-rich water (HRW) on IFG subjects and explore the underlying mechanism involved. Methods: Seventy-three pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Not only that, HRW may play an important role in reducing body fat and reducing fatty liver. This suggests its potential as a therapeutic intervention to improve lipid metabolism and liver health [102].…”
Section: Effects Of H 2 On Metabolic Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Not only that, HRW may play an important role in reducing body fat and reducing fatty liver. This suggests its potential as a therapeutic intervention to improve lipid metabolism and liver health [102].…”
Section: Effects Of H 2 On Metabolic Syndromementioning
confidence: 99%
“…Clinical data suggest that H 2 may improve glucose metabolism by interfering with the gut microbiota of impaired fasting glucose patients [102]. Another study in patients with clinical stage IV colorectal cancer found that H 2 inhalation activated PGC-1α expression and enhanced mitochondrial activity, thereby reducing the proportion of PD-1 and CD8 + T cells.…”
Section: Effects Of H 2 On Digestive System Diseasesmentioning
confidence: 99%
“…So far, the modulation of microbiota was indicated as a part of the mechanism of hydrogen treatment, and has shown potential for treating alcoholic hepatitis, 102 NAFLD, 16,105 IBD, 107 colitis, 108 muscle fatigue, 113 cholangiofibrosis, 114 metabolic syndrome, 104 diabetes mellitus, 115 and sepsis. 103,116…”
Section: Mechanisms Of Hydrogen Therapymentioning
confidence: 99%